Modified Volar Oblique Triangular Flap for Coverage of Fingertip Defects - Islam, Md Salek Bin; Nazneen, Afroza; Iqbal, Ahmed Asif; Khan, Md Noazesh; Sarkar, Asim; Md Jalaluddin, - (TAJ: Journal of Teachers Association, 2021)
Fingertip includes the portion of the digit which is distal to the insertion of flexor digitorum profundus (FDP) tendon and the extensor tendon. It is the most vulnerable part of the hand to be injured. So, reconstruction of this part requires a good outcome in sensation and function. To meet the goal of the reconstruction principle, "Like with Like" local flap is the most preferable. Such type of flap is a Volar oblique triangular flap based on volar perforator vessels from the Digital artery proper. The aim of the study is to identify its reconstruction outcome in viability, sensation, range of movement of DIPJ, and patients' satisfaction regarding contour. This was a prospective observational study; ten patients were included who were admitted in the Burn and Plastic surgery Department of Rajshahi Medical College Hospital, Rajshahi, from September 2019 to December 2020. Thirteen flaps were harvested to cover for the fingertip defect of ten patients; among them, three were female. The age range of our operated patient was 2- 38 years. None of the flaps was lost except marginal necrosis or epidermal loss. The range of movement of DIPJ and 2SPD were within the normal limit. Patients were satisfied with their contour. So, the modified volar oblique, triangular flap is one of the good options for fingertip defects. TAJ 2021; 34: No-1: 63-69